E-mail filter with attachment scanning prototype / Hema Losini Goval - Hema, Losini Goval (2001)
The E-mail Filter is a mail client that retrieves mails from the Ms Outlook Express, which retrieves mails from POP3 server and categorizes them into different a category that has different level of priorities. Attachments in the incoming mails are scanned and sent to respective folders. These attachments will be stored in the personal computer for easy reference. Meanwhile, the automatic response system automatically replies the mails classified in the Appointments category using automatic response, which runs even when the e-mails are closed. The E-mail Filter with Attachment Scanning Prototype is a stand-alone system. It has a user-friendly concept and has an interesting and simple to understand user interface. It gives the user more options to manage the mails that flow into the account. The objective of the system is to save time and cost of the user. This is because user does not have to open all folders to see what are the important folders and does not have to reply to most of the appointments by going through the manual planner. It is all done by the mail client and updated automatically. This helps to create a paperless environment. The methodology used to develop this system is the 'V' Model and it will be developed using Micro oft Visual Basic 6.0, Ms Access 2000 on a Window 2000 platform which runs from Ms Outlook Express. This system will be of a great help to reduce the burden of checking and replying mail for professional staff such as lecturer.